FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN INVOLUSIO UTERUS PADA IBU POST PARTUM 6 JAM DI UPTD PUSKESMAS TANGGEUNG TAHUN 2017 - Triana Indrayani (Jurnal Ilmu dan Budaya, 2017)
Involution of uterine shrinking is a process whereby the uterus returns to pre-pregnancy conditions weighing about 60 grams. This process begins as soon as the placenta is born due to contraction of the smooth muscles of the uterus. The purpose of this study is to determine factors. Factors associated with Involutiono Uterus on Post Partum 6 th  women in UPTD  Tanggeunghealth center Cianjur Regency Year 2017. This study used a cross sectional research design that looks for the dependent variable relationship involution of the uterus with independent variables Initiation Of Early Breastfeeding (IMD), early mobilization, nutritional status, parity and post partum mother's age. This type of research uses primary data taken directly from respondents. The population in this research is 52 postpartum, sampling technique in this research use total sampling.The prevalence of normal uterine involution is 40 people (76.9%), IMD counted 37 people (71.2%), the majority of post-partum mother 6 hours with good early mobilization of 46 people (88.5%), nutritional status No KEK as many as 44 people (84.6%), multiparity parity as many as 41 people (78.8%) and age 20-35 years as many as 43 people (82.7%). There was a significant correlation between involution of uteri in 6-hour post-partum mother with IMD (ρ value = 0,002), early mobilization (ρ value = 0,021), nutritional status (ρ value = 0,000) and parity (ρ value = 0,003). Based on the results of the study can be concluded there is a relationship between the involution of the uterus is IMD, early mobilization, nutritional status and parity. Researchers suggest improving the quality of health services with midwives providing KIE and counseling about the importance of early mobilization, IMD and nutritional status to the involution process and encouraging mothers to avoid having maternity at risk (<20 years> 35 years) and grandemuliparity parity because it can be harmful to mother.